Trends in bacteriological profile of neonatal sepsis in Neonatal Intensive Care Unit of a referral center of western Nepal - Bhandari, Bikash; Panthee, Kiran; KC, Prabal; Siddique, Neha (Journal of Kathmandu Medical College, 2020)
Background: Neonatal sepsis is one of the major causes of neonatal morbidity and mortality in developing countries like Nepal. In order to lower the morbidity and mortality of newborns in Neonatal Intensive Care Unit (NICU), it is essential to study the bacteriological profile and antibiotic sensitivity. Objective: This study aims to study the common bacteriological profile and their antibiotics susceptibility pattern in the NICU of medical college of western Nepal. Methodology: A descriptive cross-sectional study was conducted in NICU of Devdaha Medical College and Research Institute, Nepal among all blood culture positive neonates admitted between April 2020 to September 2020. Convenient sampling was done. All clinically suspected neonates were identified and laboratory data including bacteriological profile and antibiotic sensitivity were recorded and analyzed using Statistical Package for the Social Sciences (SPSS) version 20. Results: Among 215 neonates admitted in the NICU, 45 (20.9%) had culture positive sepsis. Most isolates were early onset sepsis (62.22%) and low birth weight (57.78%). The majority of isolates were Gram positive, predominantly Staphylococcus aureus (37.78%). Staphylococcus aureus showed higher resistance to Cloxacillin (57.1%) and had higher sensitivity to Vancomycin and Linezolid (100%). Similarly, Gram negative isolates, Escherichia coli and Klebsiella sps, showed higher resistance to Ceftriaxone (100%) and Cefoperazone and were highly sensitive to Imipenem (100%) and Colistin (100%). Conclusion: Staphylococcus aureus was the most common organism causing neonatal sepsis in current study with increasing resistance to commonly used Cloxacillin and Ampicillin and highly sensitive to Vancomycin and Linezolid. There is higher risk of emergence of antibiotic resistance. Thus, rational use of empirical antibiotics is necessary to prevent drug resistant sepsis.